Effects of distribution of sugars and organic acids on the taste of strawberries. Issue 7 (13th June 2019) - Ikegaya, Atsushi; Toyoizumi, Tomoyasu; Ohba, Seiji; Nakajima, Teruko; Kawata, Tomoaki; Ito, Seiko; Arai, Eiko
Abstract: The concentrations of sugars and organic acids as well as the total soluble solid (TSS) in different parts of the strawberry fruit were characterized. The data were used to create simulated fruit juice jellies, in order to clarify how the sugar and organic acid levels affect the taste. Such an approach eliminates the influence of external factors such as size, color, and texture when using real fruits in sensory evaluations. Further, the use of a jelly allowed us to simulate the concentration differences between various parts of the fruit. In the strawberry fruit, the sugar content is higher in the apex than in the peduncle; however, the level of organic acids is the same throughout. It was revealed that the sweetness and sourness in the apex and peduncle could be sufficiently recognized by humans as tastes. Also, a layered jelly sample replicating the sugar and acid distribution in real strawberry was perceived as less sweet and more sour, compared to a homogeneous one with the same overall composition. The likely reason is that the sourness in the peduncle is accentuated by the low TSS level, which decreases the TSS/total organic acid ratio that affects the sweetness/sour perceptions. Based on these results, factors for the appropriate sensory evaluation of fresh fruits in general were considered. Specifically, the distribution of sugars and organic acids in the fruit should be analyzed first, and bite‐sized parts with concentrations close to the average provide the most accurate evaluation results. Abstract : We conducted sensory evaluation using simulated fruit juice jellies prepared using foodstuffs and food additives, based on the sugar and acid contents measured in real strawberry fruits. The differences in sugar and acid concentrations between the apex and peduncle were found to have recognizable effects on the taste. Also, the sugar and acid distribution in real strawberry was perceived as less sweet and more sour, compared to a homogeneous one with the same overall composition.